Prediction Model of Build Rate of Push-the-Bit Rotary Steerable System. (22nd May 2020) - Wang, Meishan; Li, Xiaojun; Wang, Ge; Huang, Wenjun; Fan, Yongtao; Luo, Wei; Zhang, Jiange; Zhang, Junfeng; Shi, Xiaolei
Abstract : The accurate prediction of build rate of rotary steerable system (RSS) is the prerequisite for the precise control of wellbore trajectory and optimal design of the steerable tool. Push-the-bit RSS refers to a steerable drilling system that controls well trajectory through adjustment of stretch length of pushing block. Based on this feature, a three-dimensional mechanical model of push-the-bit RSS is established on the basis of the conventional steerable tool mechanical model while considering pushing force. Meanwhile, the effects of bit cutting performance and formation anisotropy are considered. Next, the lateral force method, inclination trend angle method, and ultimate build rate method based on zero lateral force are analyzed and a new ultimate build rate method based on zero lateral drilling penetration is built. A conversion coefficient is introduced to reflect the ratio of actual build rate to theoretical build rate. At last, the new model is applied to a case study. The new method is superior to other previous methods, because the effects of bit-rock interaction and actual drilling process are sufficiently considered. The influence mechanism of build rate includes "leverage effect, " "pendulum effect, " and "pushing effect." The build rate of steerable tool is a comprehensive outcome of various effects, of which the "pushing effect" plays a dominant role. With the increase of weight on bit (WOB), the proportion of "leverage effect" increases, while the proportion of "pushing effect" decreases, and therefore the build rate decreases.